Получение ультрадисперсных порошков молибдена высокой чистоты для готовления дисперсно-упрочненных наночастицами связок на основе Fe–Co–Cu–Sn и Fe–Co–Cu–WC - Воробьева, М.В.; Курбаткина, В.В.; Иванов, В.В.; Едренникова, Е.Е.; Сидоренко, Д.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
A procedure for the production of high-purity superdispersed molybdenum powders of controlled grain-size composition by hydrogen-nitrogen recovery of ammonium paramolybdate has been developed. An optimum regime of the recovery process has been proposed to ensure the production of narrow-fractional (the main fraction content id not less than 70%) molybdenum powders of 4–5 N (10–100 ppm) purity for making Fe–Co–Cu–Sn and Fe–Co–Cu–WC based binders dispersion- reinforced with nanoparticles. Peculiarities of the effect of superdispersed molybdenum particles on the production procedure, mechanical and tribological properties of Fe–Co–Cu–Sn and Fe–Co–Cu–WC based composite materials, obtained by powder metallurgy techniques, has been examined. It is shown that dispersion-strengthened binders fabricated by hot pressing feature high mechanical and tribological properties.